Pengaruh Budaya Organisasi Terhadap Produktivitas Kerja Pegawai Melalui Komitmen Organisasi Sebagai Variabel Mediasi Pada Balai Prasarana Permukiman Wilayah Sumatera Utara - Zega, Maria Helni; Karim, Ahmad; Rizki, Ainur (Journal of Innovative and Creativity, 2026)
The purpose of this study is to analyze the effect of organizational culture on employee work productivity through organizational commitment as a mediating variable at the North Sumatra Regional Settlement Infrastructure Center. This study employed a quantitative research approach. The population consisted of 175 employees, while the sample included 64 respondents. The sampling technique used in this study was the Slovin formula. The data analysis techniques included hypothesis testing, namely the partial test (t-test), coefficient of determination test (R²), and Sobel test, using SPSS 26. The results of this study indicate that organizational culture partially has a positive and significant effect on employee work productivity. Organizational culture also has a positive and significant effect on organizational commitment. Furthermore, organizational commitment has a positive effect on employee work productivity. The findings also show that organizational culture has a significant effect on employee work productivity through organizational commitment as a mediating variable.